Exploring the delayed effects of leadership coaching: a pilot study. Issue 2 (3rd July 2019) - Spence, Gordon B.; Stout-Rostron, Sunny; Reenen, Michelle Van; Glashoff, Ben
ABSTRACT: Little empirical attention has been directed towards learning as an aspect of the coaching process. Given its deeply reflective nature, it seems likely that learning is not always immediately secured psychologically by clients or successfully translated into behaviour. However, delayed effects have yet to be explicitly studied in coaching outcome research. To examine this, a pilot study was conducted to investigate the prevalence and progression of such effects following participation in a 10-week leadership coaching programme. Semi-structured interviews were conducted with 15 leaders to obtain personal narratives of their coaching experience and narrative enquiry applied to analyse the underlying phenomena. The data confirmed that coaching was immediately beneficial in a variety of ways (e.g. improved communication style), whilst also indicating that some client learning required a period of incubation, or a triggering event(s), before it became manifested in behaviour. Whilst delayed effects were not reported by all participants, initial evidence now exists to show that coachees can require time to clarify, consolidate and enact personal learning facilitated during coaching. In interpreting these results, theories of transformational learning are discussed, along with a modelling of factors that might influence the emergence of delayed effects. Recommendations for future research are also provided.